Spectrophotometric Determination of Silver (I) by Adsorption of its 1-Alkyl-3-(5-Choloro-2-Pyridyl) Thiourea Complex on Microcrystalline Naphthalene - Mathur, Priya; Mathur, S.P.; Gupta, B.D. (Asian Journal of Chemistry, 2010)
The spectrophotometric determination of trace silver(I) with 1-allyl-3-(5-chloro-2-pyridyl) thiourea is described. A stable complex formed from silver and 1-allyl-3-(5-chloro-2-pyridyl) thiourea can not be directly extracted into benzene or chloroform, but can be easily adsorbed on microcrystalline naphthalene at room temperature. This complex is dissolved in dimethylformamide solution. The absorbance of solution was measured at 430 nm against the reagent blank. Beer's law was obeyed in the concentration range 7-120 μg of silver(I) in 10 ml of dimethylformamide. The molar absorptivity was found to be 3.18 x 104 l mol–1cm–1 and sensitivity being 1.591 x 10–2 μg cm–2 of silver for the absorbance of 0.001.